Archaeotypical Language - Romero Vicuña, Miguel (Revista Universidad de Guayaquil, 2008)
A comprehensive description is made of the origin and psychophysiological evolution of the archetypes of the collective unconscious that are the prototypes of the ideas and eternal models of things and that are programmed in the hereditary genomes of each of the living beings on earth. Plants are born with their biocybernetic programs based on archetypal biological models and develop their own biological programs for each species. Animals inherit their biological archetypes of behavior that are unique to each species. And according to Jung, archetypes in man are typical forms of hereditary behavior of a universal nature that, when they become conscious, manifest as representations and experiences, like all those that become contents of consciousness. Among the main archetypes that man has are: the biological archetypes of the shadow, the animal, the elderly, the wise, (patriarch, prophet), transcendence, messianity, death, anima, animus, to the mythological, sociological, religious and philosophical. A description is also made of the way in which psychobiological processes originate and evolve in the child based on collective archetypes; Because in the human unconscious there exists a universe similar to the cosmos, where the sun, the moon, the stars and the galaxies shine, which are the oral symbols in man, caused by the oral trauma of the newborn, and which is based on the visual hallucination that appears in a state of starvation, thirst and hunger during the breastfeeding season. Finally, a study is made of the major archetypes, which are contradictory and paradoxical and which revolve around the human qualities of good and evil. With this the authors demonstrate that the archetypal images that, without being gods projected in the sky of universal consciousness, constitute the true images of what we were, are and will be in the future.